Clinical and cost-effectiveness of an online-delivered group-based pain management programme in improving pain-related disability for people with persistent pain—protocol for a non-inferiority randomised controlled trial (iSelf-help trial) - Anthony Dowell; Sarah Gerard Dean; Leigh Hale; Andrew R Gray; Tristram Ingham; Bernadette Jones; Cheryl Davies; Rebecca Grainger; William Leung; Meredith Perry; Hemakumar Devan; Dagmar Hempel; et al. (BMJ Open)
Introduction Persistent non-cancer pain affects one in five adults and is more common in Māori—the Indigenous population of New Zealand (NZ), adults over 65 years, and people living in areas of high deprivation. Despite the evidence supporting multidisciplinary pain management programmes (PMPs), access to PMPs is poor due to long waiting lists. Although online-delivered PMPs enhance access, none have been codesigned with patients or compared with group-based, in-person PMPs. This non-inferiority trial aims to evaluate the clinical and cost-effectiveness of a cocreated, culturally appropriate, online-delivered PMP (iSelf-help) compared with in-person PMP in reducing pain-related disability.Methods and analysis Mixed-methods, using a modified participatory action research (PAR) framework, involving three phases. Phase I involved cocreation and cultural appropriateness of iSelf-help by PAR team members. Phase II: The proposed iSelf-help trial is a pragmatic, multicentred, assessor-blinded, two-arm, parallel group, non-inferiority randomised controlled trial. Adults (n=180, age ≥18 years) with persistent non-cancer pain eligible for a PMP will be recruited and block randomised (with equal probabilities) to intervention (iSelf-help) and control groups (in-person PMP). The iSelf-help participants will participate in two 60-minute video-conferencing sessions weekly for 12 weeks with access to cocreated resources via smartphone application and a password-protected website. The control participants will receive group-based, in-person delivered PMP. Primary outcome is pain-related disability assessed via modified Roland Morris Disability Questionnaire at 6 months post intervention. Secondary outcomes include anxiety, depression, stress, pain severity, quality of life, acceptance, self-efficacy, catastrophising and fear avoidance. Data will be collected at baseline, after the 12-week intervention, and at 3 and 6 months post intervention. We will conduct economic analyses and mixed-method process evaluations (Phase IIA).Ethics and dissemination The Health and Disability Ethics Committee approved the study protocol (HDEC18/CEN/162). Phase III involves dissemination of findings guided by the PAR team as outcomes become apparent.Trial registration number ACTRN 12619000771156.